Karakterisasi reaktor plasma lucutan berpenghalang dielektrik berkonfigurasi elektroda spiral-silinder dengan sumber udara bebas - Istiqomah Istiqomah; Muhammad Nur; Fajar Arianto (Youngster Physics Journal, 2017)
A research about  characteristics of the plasma reactor dielectric barrier discharge gas filling the air. Plasma reactor in this research was prepared by component an electrode in the form of copper wire wrapped with a number of turns as much as 72 coil and coil diameter 25,05 mm, pyrex tube with a length of 30 cm, a diameter of 3 cm, and a thickness of 2,45 mm as a dielectric barrier, and the outer electrode in the form of cooper sheet the loaking the pyrex tube. This characterization is done by the air stream into the reactor without sample. Input voltage variation used 0,2-1,4 kV at intervals rise of 0,2 kV and the air flow rate 1-10 L/min with intervals increase of 1 L/min. The results of the characterization of current and voltage is obtained, the greater the measured current with increasing voltage and air flow rate given. The result of the characterization can be used to calculate the value of the charge carrier mobility, and the charge carrier mobility values obtained on the air flow rate 1-8 L/min increased along with the increase in air flow rate. Mobility values in the lowest obtained by air flow rate 2 L/min and the highest air flow rate 8 L/min at 2,59 x 10-5 m2/Vs and 6,08 x 10-5 m2/Vs. In addition, there are also ozone measured from the reactor stuffing free air, and obtained the maximum ozone concentration in the air flow rate of 10 L/min at 191,698 ppm.Keywords: the plasma dielectric barrier discharge, ozone, mobility of the charge carriers